Métagénomique des tapis microbiens polaires - Varin, Thibaut (Université Laval, 2013)
Over the last few years, metagenomics and next generation sequencing (NGS) have been revolutionizing the field of microbial ecology leading to a greater understanding of the structure and functions of the microbial communities in the biosphere. The work presented here applies these new technologies to study polar microbial mats, which are poorly-characterized ecosystems. Metagenomic analyses of distinct polar microbial mats provided an opportunity to, firstly obtain a general description of microbial community composition and metabolic activity, and subsequently, to more thoroughly study two specific metabolic processes. We hypothesized that microbial mats are nutrient-replete despite the oligotrophic conditions of the surrounding waters due to strong nutrient recycling within the polar microbial mats. Analyses of metagenomic profiles derived from arctic microbial mats revealed that several groups of genes involved in scavenging mechanisms provide these communities with the capacity to retain and recycle nutrients within the shallow benthic microenvironment. Another aspect of polar microbial mats which was examined during this PhD, addresses the ability of organisms in the mat to thrive despite varied environmental stresses. The presence of different metabolic processes involved in cold adaptation and other stresses was detected from metagenomic analyses of Arctic and Antarctic communities that were consistently proportional to their representation within major bacterial groups. This thesis demonstrates how metagenomics and associated « meta-omics » approaches can be informative to improve global comprehension of microbial ecology, and how the emergence of these disciplines enables us to tackle fundamental questions such as biogeography of microorganisms with a new vision. Le domaine de l'écologie microbienne est en pleine effervescence grâce à l'avènement de la métagénomique et des techniques de séquençage de nouvelle génération (SNG), qui nous apportent une meilleure compréhension de la structure et du ...